The crime of human trafficking and its view on criminal policy currently - Larico Portugal, Jorge (2021)
The crime of trafficking in persons is the third crime that generates the greatest economic revenue, preceded by illicit drug trafficking and arms trafficking, such economic revenue directly influences its increasing incidence; and, taking into consideration its high criminal incidence, the ways of perpetrating this crime are increasing, becoming more complex, erecting new mechanisms for its perpetration, adapting to each population and social group. This is why, due to its high incidence, a detailed study of this crime is required. In this paper we will develop relevant aspects of human trafficking; we will also address its typical structure, its typical modalities, its criminal means, aggravating factors and other aspects. In addition, we will analyze the main international and national jurisprudential rulings on the crime of trafficking in persons. Finally, we will develop the policies or actions of criminal policy on human trafficking, whose character is preventive, punitive and preservation, and its purpose is to control, reduce and eradicate all exploitation of human beings.